2023
DOI: 10.1002/chem.202302457
|View full text |Cite
|
Sign up to set email alerts
|

The Field of Main Group Lewis Acids and Lewis Superacids: Important Basics and Recent Developments

Alexey Y. Timoshkin

Abstract: New developments in the field of Lewis acidity are highlighted, with the focus of novel Lewis acids and Lewis superacids of group 2, 13, 14, and 15 elements. Several important basics, illustrated by modern examples (classification of Donor‐Acceptor (DA) complexes, amphoteric nature of any compound in terms of DA interactions, reorganization energies of main group Lewis acids and the role of the energies of frontier orbitals) are presented and discussed. It is emphasized that the Lewis acidity phenomena are gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 242 publications
0
0
0
Order By: Relevance
“…We have shown that a two-channel activation by the means of a strongly electrophilic bis(borane) C 6 F 4 {B(C 6 F 5 ) 2 } 2 ( B 2 CF ) imparts significant activation to the diatomic molecule, up to the diazene-diide (N 2 2− ) state. 40 In the continuation of this work, we decided to study the coordination of the aluminium analogue of BCF , tris(pentafluorophenyl)alane – Al(C 6 F 5 ) 3 ( AlCF ) 47–56 – to group 6 dinitrogen complexes, in order to assess how the resulting Lewis pairs differ or not in terms of structure and reactivity with respect to BCF .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that a two-channel activation by the means of a strongly electrophilic bis(borane) C 6 F 4 {B(C 6 F 5 ) 2 } 2 ( B 2 CF ) imparts significant activation to the diatomic molecule, up to the diazene-diide (N 2 2− ) state. 40 In the continuation of this work, we decided to study the coordination of the aluminium analogue of BCF , tris(pentafluorophenyl)alane – Al(C 6 F 5 ) 3 ( AlCF ) 47–56 – to group 6 dinitrogen complexes, in order to assess how the resulting Lewis pairs differ or not in terms of structure and reactivity with respect to BCF .…”
Section: Introductionmentioning
confidence: 99%
“…In ascending order, the latter has an FIA higher than B 2 CF (523 kJ mol −1 ), SbF 5 (490 kJ mol −1 ) (the reference of the LSA scale), and much higher than BCF (450 kJ mol −1 ). 53,56,62–65…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation